Antihiperglikemik Kombinasi Minyak Biji Mahoni (Swietenia mahogani (L.) Jacq-Glibenklamid pada Tikus Diinduksi Aloksan - DIONYSIUS ANDANG ARIF WIBAWA; KETUT WIRIANA; LUCIA VITA INANDHA DEWI; RATNA AGUNG SAMSUMAHARTO (Fakultas Farmasi Universitas Pancasila, 2017)
Diabetes mellitus (DM) is a chronic disorder metabolism of glucose in the body. Mahogany seeds (Swietenia mahagoni (L.) Jacq.) reportedly contains fl avonoids, alkaloids and saponins which can be used as therapy of diabetes mellitus. This study aimed to determine the eff ects of antihyperglycemic combination of mahogany seed oil-glibenclamide in male rats hyperglycemiced by alloxan induction. The mahogany seed oil liquefaction processed by using hydrolic pressed instrument 100 psi pressure. This study using Wistar strain male rats aged 2-3 months as many as 35 heads which were divided into 7 groups: group I (normal control) with distilled water added, while the II-VII group with alloxan induced intraperitoneal 140 mg/kg body weight two times. Group II as a negative control was added 0.5% CMC, group III was added glibenclamide 0.09 mg/200 g BB, IV groups oiled mahogany seeds 2 mL/200 g BW, group V, VI, and VII were added a combination of mahogany seed oil glibenclamide with each ratio (75%: 25%, 50%: 50%, 75%: 25%). The distribution of the test preparation 1 times a day for 12 days and blood glucose measurement performed on days 3, 6, 9, and 12. Data has been analyzed by oneway ANOVA (signifi cant p <0.05). The results obtained the combination of mahogany seed oil-glibenclamide provides eff ect to reduction in blood glucose levels induced male rats alloxan, the combination group mahoni-glibenclamide seed oil have equal activity in lowering blood glucose levels with a single chemical drug glibenclamide. Mahogany seed oil is potentially antidiabetic.